How Was The Role of Human Resource Planning in The Quality of Production Process at Nédirzanit Company - Azizah, Ummi; Bekti, Rudy (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. The quality of the products produced by a company is determined based on certain measurements and characteristics based on the standards set by the company. NÉDIRZANIT is a fashion company that put forward the theme of literature and its illustrations. NÉDIRZANIT has a problem of low quality production processes where production errors often occur. This results in decreased product quality or even defective products. Therefore, this research is conducted with an aim to discover the factors causing the low quality of the production process in terms of human resource planning and find out solutions to improve the quality of the production process. The research method used is qualitative descriptive analysis. This study was conducted by interviewing the workers. The data obtained is processed By using manual coding. The result, it can be seen that the factor causing the low quality of the production process is the low priority to production task. The solution to overcome the low quality of the production process is to make human resource planning with mature and structured in order to be able to manage the human resources owned by utilizing their maximum potential. Keywords: human resource; human resource planning; production management; quality of production process; defect product